Treatment of endothelial cell dysfunction in atherosclerosis: a new perspective integrating traditional and modern approaches - Luqun Yang; Xinjian Li; Lin Ni; Yuanyuan Lin (Frontiers in Physiology)
Atherosclerosis (AS), a prime causative factor in cardiovascular disease, originates from endothelial cell dysfunction (ECD). Comprising a vital part of the vascular endothelium, endothelial cells play a crucial role in maintaining vascular homeostasis, optimizing redox balance, and regulating inflammatory responses. More evidence shows that ECD not only serves as an early harbinger of AS but also exhibits a strong association with disease progression. In recent years, the treatment strategies for ECD have been continuously evolving, encompassing interventions ranging from lifestyle modifications to traditional pharmacotherapy aimed at reducing risk factors, which also have demonstrated the ability to improve endothelial cell function. Additionally, novel strategies such as promising biotherapy and gene therapy have drawn attention. These methods have demonstrated enormous potential and promising prospects in improving endothelial function and reversing AS. However, it is essential to remain cognizant that the current treatments still present significant challenges regarding therapeutic efficacy, long-term safety, and ethical issues. This article aims to provide a systematic review of these treatment methods, analyze the mechanisms and efficacy of various therapeutic strategies, with the goal of offering insights and guidance for clinical practice, and further advancing the prevention and treatment of cardiovascular diseases.